Preparation method of high-specific-surface partition plate of storage battery
By using modified glass fibers and nano-silica during the preparation of AGM separators, the specific surface area and acid absorption capacity of the separators are improved, and the problem of insufficient acid absorption capacity of the existing AGM separators is solved, and the stability of battery capacity is improved.
Patent Information
- Application Number
- CN202510144821.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-10
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-02-10
AI Technical Summary
The specific surface area of existing AGM partitions is generally low, resulting in insufficient acid absorption capacity and affecting the stability of battery capacity.
By adding glass fibers, modified glass fibers and nanosilicon dioxide to water to beat them to form fiber slurry, and after multiple wet treatments and drying treatments, a battery separator with a high specific surface area was prepared.
The specific surface area and acid absorption capacity of the partition are improved, and the stability and uniformity of the network structure of the partition are enhanced, thereby improving the capacity stability of the battery.
Smart Images

Figure BDA0005266119100000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of storage batteries, and in particular relates to a method for preparing a high-specific surface area separator of a storage battery. Background Art
[0002] The battery separator is one of the important components of the battery. Its main function is to prevent the positive and negative electrodes from short-circuiting, while promoting electrochemical reactions, improving battery performance and extending battery life. The separator is located between the positive and negative plates to prevent direct contact, while ensuring the normal movement of ion migration, so that the ions in the battery circuit are conductive and unobstructed.
[0003] At present, the commonly used battery separators in China mainly include rubber separators, AGM separators, PVC separators and PP separators. Among them, AGM separators (absorbent glass fiber separators) have become a new and widely used material due to their excellent mechanical properties, physical properties and high cost performance. With the continuous advancement of science and technology, as well as the development of petroleum, chemical industry and materials science, the application scope of glass fiber separators (AGM separators) has become more and more extensive, gradually becoming a key material in the battery industry, and developing into mainstream separators in the field of batteries.
[0004] The specific surface area of the AGM separator has an important influence on its comprehensive performance. At present, AGM separators are usually prepared by a wet process from fine glass fibers with a diameter of less than 1.2μm, coarse glass fibers with a diameter of 2-11μm, and a small amount of organic fibers. Although increasing the amount of fine glass fibers can increase the specific surface area of the AGM separator to a certain extent, the price of fine glass fibers is relatively high, resulting in increased costs. Therefore, in actual production, it is necessary to weigh the amount of fine fibers to balance performance and cost. In the prior art, the specific surface area of AGM separators is generally low, generally at 0.8-1.4㎡ / g. Increasing the specific surface area of the separator is beneficial to increasing the acid absorption of the separator. The more acid is absorbed, the less acid stratification occurs, and the capacity of the battery is stable. Therefore, it is necessary to prepare a separator with a high specific surface area. Summary of the invention
[0005] In order to solve the above problems, the object of the present invention is to provide a method for preparing a high specific surface area separator for a battery.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A method for preparing a high specific surface area separator for a battery comprises the following steps:
[0008] S1. Add glass fiber, modified glass fiber and additives into water, beat at a speed of 1000 rpm for 30-60 min to obtain fiber slurry, and add water to adjust the pH value of the fiber slurry to 1-2;
[0009] S2, filtering and dehydrating the fiber slurry obtained in S1 to obtain a primary wet separator;
[0010] S3, coating the nano-silicon dioxide solution on the surface of the primary wet partition for 1-2 hours to obtain a treated wet partition;
[0011] S4, filtering and dehydrating the treated wet partition to obtain a secondary wet partition;
[0012] S5. Dry the secondary wet separator at 120° C. for 8-10 min to obtain a battery high specific surface area separator.
[0013] Further, the modified glass fiber in step S1 is prepared by the following steps:
[0014] S11, dissolving polyacrylamide in ethylene glycol to obtain a polyacrylamide solution;
[0015] S12, dispersing the glass fiber into the polyacrylamide solution and immersing for 60-90 minutes;
[0016] S13, filtering and separating the glass fibers and then drying them to obtain modified glass fibers.
[0017] Furthermore, the mass concentration of the polyacrylamide solution is 10-20%; the amount of glass fiber used is 0.3-0.5% of the mass of the polyacrylamide solution.
[0018] Furthermore, the additives in step S1 are dispersants, retention aids and filter aids; the dispersant is one of sodium alginate, polyethylene glycol and potassium pyrophosphate; the retention aid is one of alum, bentonite and chitosan; and the filter aid is diatomaceous earth.
[0019] Furthermore, in step S2, the filtration pressure is 0.02-0.03 MPa, and the dehydration time is 2-5 s.
[0020] Furthermore, the moisture content of the primary wet partition in step S2 is 60-65%.
[0021] Further, the nano-silicon dioxide solution in step S3 is prepared by the following steps:
[0022] Add nano-silicon dioxide into water and beat it at a speed of 1000 rpm for 30-60 minutes to obtain a nano-silicon dioxide solution; the nano-silicon dioxide has a particle size of 1-1.5 nm and a specific surface area of 500-600 m 2 / g.
[0023] Furthermore, in step S4, the filtration pressure is 0.03-0.06 MPa, and the dehydration time is 6-10 s.
[0024] Furthermore, the water content of the secondary wet partition in step S4 is 55-60%.
[0025] Furthermore, the high specific surface area separator of the battery includes 80% of glass fiber, 5-10% of modified glass fiber, 0.5-1% of additives and 5-10% of nano silicon dioxide.
[0026] Beneficial effects of the present invention:
[0027] (1) The present invention uses polyacrylamide-modified glass fibers when preparing battery separators, which can enhance the internal cross-linking of the separators and form a network structure with the glass fibers, thereby increasing the specific surface area of the separators and improving the acid absorption capacity of the separators.
[0028] (2) The present invention uses nano-silicon dioxide when preparing battery separators. Nano-silicon dioxide has a high specific surface area, which is beneficial to maintaining the stability and uniformity of the separator network structure and improving the acid absorption capacity of the separator. Nano-silicon dioxide can form a rich multi-porous network structure in the glass fiber under acidic conditions, which is beneficial to the preparation of separators with high specific surface area. DETAILED DESCRIPTION
[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Example 1
[0031] This embodiment provides a method for preparing a high specific surface area separator for a battery, comprising the following steps:
[0032] S1, adding glass fiber, modified glass fiber, dispersant sodium alginate, retention aid alum and filter aid diatomaceous earth into water, beating at a speed of 1000 rpm for 40 minutes to obtain fiber slurry, and adding water to adjust the pH value of the fiber slurry to 1-2;
[0033] S2, filtering and dehydrating the fiber slurry obtained in S1, the filtering pressure is 0.03MPa, the dehydration time is 5s, and a primary wet separator with a water content of 60% is obtained;
[0034] S3, coating the nano-silicon dioxide solution on the surface of the primary wet partition plate for 2 hours to obtain a treated wet partition plate;
[0035] S4, filtering and dehydrating the treated wet partition, the filtering pressure is 0.05MPa, the dehydration time is 8s, and a secondary wet partition with a water content of 55% is obtained;
[0036] S5. Dry the secondary wet separator at 120° C. for 10 min to obtain a battery high specific surface area separator.
[0037] The modified glass fiber described in step S1 is prepared by the following steps:
[0038] S11, dissolving polyacrylamide in ethylene glycol to obtain a polyacrylamide solution with a mass concentration of 15%;
[0039] S12, dispersing glass fibers into the polyacrylamide solution and immersing for 90 minutes; the amount of glass fibers used is 0.4% of the mass of the polyacrylamide solution;
[0040] S13, filtering and separating the glass fibers and then drying them to obtain modified glass fibers.
[0041] The nano-silicon dioxide solution in step S3 is prepared by the following steps:
[0042] Add nano-silicon dioxide into water and beat it at a speed of 1000 rpm for 60 minutes to obtain a nano-silicon dioxide solution; the nano-silicon dioxide has a particle size of 1-1.5 nm and a specific surface area of 500-600 m 2 / g.
[0043] The high specific surface area separator of the battery includes 80% of glass fiber, 5% of modified glass fiber, 1% of additive and 5% of nano silicon dioxide.
[0044] Example 2
[0045] This embodiment provides a method for preparing a high specific surface area separator for a battery, comprising the following steps:
[0046] S1, adding glass fiber, modified glass fiber, dispersant polyethylene glycol, retention aid bentonite and filter aid diatomaceous earth into water, beating at a speed of 1000 rpm for 40 minutes to obtain fiber slurry, and adding water to adjust the pH value of the fiber slurry to 1-2;
[0047] S2, filtering and dehydrating the fiber slurry obtained in S1, the filtering pressure is 0.03MPa, the dehydration time is 5s, and a primary wet separator with a water content of 60% is obtained;
[0048] S3, coating the nano-silicon dioxide solution on the surface of the primary wet partition plate for 2 hours to obtain a treated wet partition plate;
[0049] S4, filtering and dehydrating the treated wet partition, the filtering pressure is 0.05MPa, the dehydration time is 8s, and a secondary wet partition with a water content of 55% is obtained;
[0050] S5. Dry the secondary wet separator at 120° C. for 10 min to obtain a battery high specific surface area separator.
[0051] The modified glass fiber described in step S1 is prepared by the following steps:
[0052] S11, dissolving polyacrylamide in ethylene glycol to obtain a polyacrylamide solution with a mass concentration of 15%;
[0053] S12, dispersing glass fibers into the polyacrylamide solution and immersing for 90 minutes; the amount of glass fibers used is 0.4% of the mass of the polyacrylamide solution;
[0054] S13, filtering and separating the glass fibers and then drying them to obtain modified glass fibers.
[0055] The nano-silicon dioxide solution in step S3 is prepared by the following steps:
[0056] Add nano-silicon dioxide into water and beat it at a speed of 1000 rpm for 60 minutes to obtain a nano-silicon dioxide solution; the nano-silicon dioxide has a particle size of 1-1.5 nm and a specific surface area of 500-600 m 2 / g.
[0057] The high-specific surface area separator of the battery includes 80% of glass fiber, 7% of modified glass fiber, 1% of additives and 5% of nano silicon dioxide.
[0058] Example 3
[0059] This embodiment provides a method for preparing a high specific surface area separator for a battery, comprising the following steps:
[0060] S1, adding glass fiber, modified glass fiber, dispersant potassium pyrophosphate, retention aid chitosan and filter aid diatomaceous earth into water, beating at a speed of 1000 rpm for 40 minutes to obtain fiber slurry, and adding water to adjust the pH value of the fiber slurry to 1-2;
[0061] S2, filtering and dehydrating the fiber slurry obtained in S1, the filtering pressure is 0.03MPa, the dehydration time is 5s, and a primary wet separator with a water content of 60% is obtained;
[0062] S3, coating the nano-silicon dioxide solution on the surface of the primary wet partition plate for 2 hours to obtain a treated wet partition plate;
[0063] S4, filtering and dehydrating the treated wet partition, the filtering pressure is 0.05MPa, the dehydration time is 8s, and a secondary wet partition with a water content of 55% is obtained;
[0064] S5. Dry the secondary wet separator at 120° C. for 10 min to obtain a battery high specific surface area separator.
[0065] The modified glass fiber described in step S1 is prepared by the following steps:
[0066] S11, dissolving polyacrylamide in ethylene glycol to obtain a polyacrylamide solution with a mass concentration of 15%;
[0067] S12, dispersing glass fibers into the polyacrylamide solution and immersing for 90 minutes; the amount of glass fibers used is 0.4% of the mass of the polyacrylamide solution;
[0068] S13, filtering and separating the glass fibers and then drying them to obtain modified glass fibers.
[0069] The nano-silicon dioxide solution in step S3 is prepared by the following steps:
[0070] Add nano-silicon dioxide into water and beat it at a speed of 1000 rpm for 60 minutes to obtain a nano-silicon dioxide solution; the nano-silicon dioxide has a particle size of 1-1.5 nm and a specific surface area of 500-600 m 2 / g.
[0071] The high specific surface area separator of the battery includes 80% of glass fiber, 10% of modified glass fiber, 1% of additive and 5% of nano silicon dioxide.
[0072] Example 4
[0073] This embodiment provides a method for preparing a high specific surface area separator for a battery, comprising the following steps:
[0074] S1, adding glass fiber, modified glass fiber, dispersant potassium pyrophosphate, retention aid chitosan and filter aid diatomaceous earth into water, beating at a speed of 1000 rpm for 40 minutes to obtain fiber slurry, and adding water to adjust the pH value of the fiber slurry to 1-2;
[0075] S2, filtering and dehydrating the fiber slurry obtained in S1, the filtering pressure is 0.03MPa, the dehydration time is 5s, and a primary wet separator with a water content of 60% is obtained;
[0076] S3, coating the nano-silicon dioxide solution on the surface of the primary wet partition plate for 2 hours to obtain a treated wet partition plate;
[0077] S4, filtering and dehydrating the treated wet partition, the filtering pressure is 0.05MPa, the dehydration time is 8s, and a secondary wet partition with a water content of 55% is obtained;
[0078] S5. Dry the secondary wet separator at 120° C. for 10 min to obtain a battery high specific surface area separator.
[0079] The modified glass fiber described in step S1 is prepared by the following steps:
[0080] S11, dissolving polyacrylamide in ethylene glycol to obtain a polyacrylamide solution with a mass concentration of 15%;
[0081] S12, dispersing glass fibers into the polyacrylamide solution and immersing for 90 minutes; the amount of glass fibers used is 0.4% of the mass of the polyacrylamide solution;
[0082] S13, filtering and separating the glass fibers and then drying them to obtain modified glass fibers.
[0083] The nano-silicon dioxide solution in step S3 is prepared by the following steps:
[0084] Add nano-silicon dioxide into water and beat it at a speed of 1000 rpm for 60 minutes to obtain a nano-silicon dioxide solution; the nano-silicon dioxide has a particle size of 1-1.5 nm and a specific surface area of 500-600 m 2 / g.
[0085] The high specific surface area separator of the battery includes 80% of glass fiber, 10% of modified glass fiber, 1% of additive and 7% of nano silicon dioxide.
[0086] Example 5
[0087] This embodiment provides a method for preparing a high specific surface area separator for a battery, comprising the following steps:
[0088] S1, adding glass fiber, modified glass fiber, dispersant potassium pyrophosphate, retention aid chitosan and filter aid diatomaceous earth into water, beating at a speed of 1000 rpm for 40 minutes to obtain fiber slurry, and adding water to adjust the pH value of the fiber slurry to 1-2;
[0089] S2, filtering and dehydrating the fiber slurry obtained in S1, the filtering pressure is 0.03MPa, the dehydration time is 5s, and a primary wet separator with a water content of 60% is obtained;
[0090] S3, coating the nano-silicon dioxide solution on the surface of the primary wet partition plate for 2 hours to obtain a treated wet partition plate;
[0091] S4, filtering and dehydrating the treated wet partition, the filtering pressure is 0.05MPa, the dehydration time is 8s, and a secondary wet partition with a water content of 55% is obtained;
[0092] S5. Dry the secondary wet separator at 120° C. for 10 min to obtain a battery high specific surface area separator.
[0093] The modified glass fiber described in step S1 is prepared by the following steps:
[0094] S11, dissolving polyacrylamide in ethylene glycol to obtain a polyacrylamide solution with a mass concentration of 15%;
[0095] S12, dispersing glass fibers into the polyacrylamide solution and immersing for 90 minutes; the amount of glass fibers used is 0.4% of the mass of the polyacrylamide solution;
[0096] S13, filtering and separating the glass fibers and then drying them to obtain modified glass fibers.
[0097] The nano-silicon dioxide solution in step S3 is prepared by the following steps:
[0098] Add nano-silicon dioxide into water and beat it at a speed of 1000 rpm for 60 minutes to obtain a nano-silicon dioxide solution; the nano-silicon dioxide has a particle size of 1-1.5 nm and a specific surface area of 500-600 m 2 / g.
[0099] The high specific surface area separator of the battery comprises 80% of glass fiber, 10% of modified glass fiber, 1% of additive and 10% of nano silicon dioxide.
[0100] Comparative Example 1
[0101] This comparative example provides a method for preparing a battery separator, comprising the following steps:
[0102] S1, adding glass fiber, dispersant sodium alginate, retention aid alum and filter aid diatomaceous earth into water, beating at a speed of 1000 rpm for 40 minutes to obtain fiber slurry, and adding water to adjust the pH value of the fiber slurry to 1-2;
[0103] S2, filtering and dehydrating the fiber slurry obtained in S1, the filtering pressure is 0.03MPa, the dehydration time is 5s, and a primary wet separator with a water content of 60% is obtained;
[0104] S3, coating the nano-silicon dioxide solution on the surface of the primary wet partition plate for 2 hours to obtain a treated wet partition plate;
[0105] S4, filtering and dehydrating the treated wet partition, the filtering pressure is 0.05MPa, the dehydration time is 8s, and a secondary wet partition with a water content of 55% is obtained;
[0106] S5. Dry the secondary wet separator at 120° C. for 10 min to obtain a battery separator.
[0107] The nano-silicon dioxide solution in step S3 is prepared by the following steps:
[0108] Add nano-silicon dioxide into water and beat it at a speed of 1000 rpm for 60 minutes to obtain a nano-silicon dioxide solution; the nano-silicon dioxide has a particle size of 1-1.5 nm and a specific surface area of 500-600 m 2 / g.
[0109] The battery high specific surface area separator includes 85% glass fiber, 1% additive and 5% nano silicon dioxide.
[0110] Comparative Example 2
[0111] This comparative example provides a method for preparing a battery separator, comprising the following steps:
[0112] S1, adding glass fiber, modified glass fiber, dispersant sodium alginate, retention aid alum and filter aid diatomaceous earth into water, beating at a speed of 1000 rpm for 40 minutes to obtain fiber slurry, and adding water to adjust the pH value of the fiber slurry to 1-2;
[0113] S2, filtering and dehydrating the fiber slurry obtained in S1, the filtering pressure is 0.03MPa, the dehydration time is 5s, and a primary wet separator with a water content of 60% is obtained;
[0114] S3. Drying the primary wet separator at 120° C. for 10 min to obtain a battery separator.
[0115] The modified glass fiber described in step S1 is prepared by the following steps:
[0116] S11, dissolving polyacrylamide in ethylene glycol to obtain a polyacrylamide solution with a mass concentration of 15%;
[0117] S12, dispersing glass fibers into the polyacrylamide solution and immersing for 90 minutes; the amount of glass fibers used is 0.4% of the mass of the polyacrylamide solution;
[0118] S13, filtering and separating the glass fibers and then drying them to obtain modified glass fibers.
[0119] The battery high specific surface area separator includes 85% of glass fiber, 5% of modified glass fiber and 1% of additives.
[0120] The specific surface areas of the high specific surface area separators of the batteries obtained in Examples 1 to 5 and Comparative Examples 1 to 2 were measured, and the results are shown in Table 1:
[0121] Table 1
[0122]
[0123] As can be seen from Table 1, when preparing battery separators in Examples 1 to 5, polyacrylamide-modified glass fibers and nano-silicon dioxide were added, the specific surface areas of the separators obtained were all above 6 m 2 / g or more, because on the one hand, the use of polyacrylamide-modified glass fiber in the preparation of battery separators can enhance the internal cross-linking of the separators and form a network structure with the glass, which is beneficial to increasing the specific surface area of the separators and improving the acid absorption capacity of the separators; on the other hand, the use of nano-silicon dioxide in the preparation of battery separators has a high specific surface area, which is beneficial to maintaining the stability and uniformity of the separator network structure and improving the acid absorption capacity of the separators; nano-silicon dioxide can form a rich multi-porous network structure in the glass fiber under acidic conditions, which is beneficial to the preparation of separators with high specific surface area.
[0124] Compared with Example 1, in Comparative Example 1, no polyacrylamide-modified glass fiber was added when preparing the battery separator, and the specific surface area of the obtained battery separator was smaller; compared with Example 1, in Comparative Example 2, no nano-silica was added when preparing the battery separator, and the specific surface area of the obtained battery separator was also smaller.
[0125] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0126] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a high specific surface area separator for a battery, characterized in that: The following steps are involved: S1. Add glass fiber, modified glass fiber and additives into water, beat at a speed of 1000 rpm for 30-60 min to obtain fiber slurry, and add water to adjust the pH value of the fiber slurry to 1-2; S2, filtering and dehydrating the fiber slurry obtained in S1 to obtain a primary wet separator; S3, coating the nano-silicon dioxide solution on the surface of the primary wet partition for 1-2 hours to obtain a treated wet partition; S4, filtering and dehydrating the treated wet partition to obtain a secondary wet partition; S5. Dry the secondary wet separator at 120° C. for 8-10 min to obtain a battery high specific surface area separator.
2. The method for preparing a high specific surface area separator for a battery according to claim 1, characterized in that: The modified glass fiber described in step S1 is prepared by the following steps: S11, dissolving polyacrylamide in ethylene glycol to obtain a polyacrylamide solution; S12, dispersing the glass fiber into the polyacrylamide solution and immersing for 60-90 minutes; S13, filtering and separating the glass fibers and then drying them to obtain modified glass fibers.
3. The method for preparing a high specific surface area separator for a battery according to claim 2, characterized in that: The mass concentration of the polyacrylamide solution is 10-20%; the amount of the glass fiber used is 0.3-0.5% of the mass of the polyacrylamide solution.
4. The method for preparing a high specific surface area separator for a battery according to claim 1, characterized in that: The additives in step S1 are dispersants, retention aids and filter aids; the dispersant is one of sodium alginate, polyethylene glycol and potassium pyrophosphate; the retention aid is one of alum, bentonite and chitosan; and the filter aid is diatomaceous earth.
5. The method for preparing a high specific surface area separator for a battery according to claim 1, characterized in that: In step S2, the filtration pressure is 0.02-0.03 MPa, and the dehydration time is 2-5 s.
6. The method for preparing a high specific surface area separator for a battery according to claim 1, characterized in that: The moisture content of the primary wet partition in step S2 is 60-65%.
7. The method for preparing a high specific surface area separator for a battery according to claim 1, characterized in that: The nano-silicon dioxide solution in step S3 is prepared by the following steps: Add nano-silicon dioxide into water and beat it at a speed of 1000 rpm for 30-60 minutes to obtain a nano-silicon dioxide solution; the nano-silicon dioxide has a particle size of 1-1.5 nm and a specific surface area of 500-600 m 2 / g.
8. The method for preparing a high specific surface area separator for a battery according to claim 1, characterized in that: In step S4, the filtration pressure is 0.03-0.06 MPa, and the dehydration time is 6-10 s.
9. The method for preparing a high specific surface area separator for a battery according to claim 1, characterized in that: The water content of the secondary wet partition in step S4 is 55-60%.
10. The method for preparing a high specific surface area separator for a storage battery according to claim 1, characterized in that: The high-specific surface area separator of the battery comprises 80% of glass fiber, 5-10% of modified glass fiber, 0.5-1% of additives and 5-10% of nano silicon dioxide.
Citation Information
Patent Citations
Method for preparing AGM (Absorptive Glass Met) separator with high specific surface area
CN106784536A
Preparation process of lead-acid battery separator
CN118645766A
Battery separators
GB1383190A
Acid resistant glass mats that include binders with hydrophilic agents
US20170288188A1